Efficacy of an intramuscular bivalent norovirus GI.1/GII.4 virus-like particle vaccine candidate in healthy US adults. Issue 41 (22nd September 2020) - Sherwood, James; Mendelman, Paul M.; Lloyd, Eric; Liu, Mengya; Boslego, John; Borkowski, Astrid; Jackson, Ashley; Faix, Dennis; ,
Highlights: First large in-human efficacy trial of a norovirus vaccine candidate. Low rates of homotypic (GI.1/GII.4) norovirus acute gastroenteritis. Vaccine had significant efficacy against all-type norovirus acute gastroenteritis. Some GII.2 cases in placebo recipients had immunity against vaccine GII.4c genotype. Candidate vaccine induces cross-protection against heterotypic norovirus strains. Abstract: Background: We performed this first-in-human efficacy trial of Takeda's bivalent norovirus vaccine candidate (TAK-214) against moderate or severe acute gastroenteritis (AGE) in healthy adults. Methods: This double-blind, randomized, placebo-controlled phase 2b trial was conducted over two winter seasons in 18–49 year-old US Navy recruits. Participants were randomized (1:1) to receive intramuscular injections of saline placebo (N = 2, 357) or TAK-214 [15 μg GI.1 and 50 μg GII.4c VLPs, 0.5 mg Al(OH)3 ] (N = 2, 355), and monitored for 45 days post-vaccination for AGE. Norovirus genotypes were identified by RT-PCR and sequencing of stool/vomitus samples. Sera from AGE cases were used to assess immune responses as genotype-specific histo-blood group antigen (HBGA)-blocking antibodies. Findings: With low rates of homotypic norovirus AGE detected the statistical analysis was proactively modified to account for AGE due to any norovirus genotype. Of the 48 norovirus AGE cases of "any severity", 29 in placebo and 19 in vaccinees, causative genotypes were GI.1 (n = 1), G1.7a (n = 1), GII.2 (n = 39) and GII.4 (n = 7). Applying predefined definitions of moderate or severe AGE gave 26 vs. 10 cases due to any norovirus genotype in placebo vs. vaccine groups, a vaccine efficacy (VE) of 61.8% (95.01% CI, 20.8 to 81.6; p = 0.0097). Five vs. one moderate or severe cases due to vaccine GI.1/GII.4 homotypic genotypes in placebo vs. vaccine arms gave a primary endpoint vaccine efficacy of 80.0% (99.99% CI, −1318.1 to 99.7; p = 0.142). Levels of GI.1 and GII.4 HBGA-blocking antibodies were increased in vaccinees and in some placebo AGE cases infected with GII.2, indicating cross-reactivity in the immune responses to different genotypes. Interpretation: Despite limited cases of homotypic norovirus AGE meaning the primary endpoint was not fully evaluable, we showed TAK-214 provided statistically significant efficacy against "any moderate/severe norovirus AGE" principally caused by the heterotypic GII.2 genotype, demonstrating induction of cross-genotype protection.